The Influence of Workload and Work Motivation on Employee Performance in Supporting the Effectiveness of Internal Control in Private Companies in Indonesia - Utami, Mega (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine the influence of workload and work motivation on employee performance in supporting the effectiveness of internal control in private companies in Indonesia. A quantitative research approach was applied using survey data collected from 150 employees through structured questionnaires measured on a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to evaluate both measurement and structural models, including validity, reliability, and hypothesis testing. The findings reveal that workload has a significant negative effect on employee performance, indicating that excessive task demands may reduce productivity and hinder employees’ ability to maintain consistent performance standards. In contrast, work motivation demonstrates a strong positive influence, suggesting that psychological encouragement, recognition, and supportive leadership play crucial roles in enhancing performance outcomes. Furthermore, employee performance significantly improves the effectiveness of internal control systems, reflecting how competent and motivated employees contribute to better monitoring, compliance, and organizational governance practices. These results emphasize the need for organizations to balance job demands with motivational strategies, such as fair workload distribution, performance feedback, and career development opportunities. The study contributes to the literature by integrating human resource management variables with internal control effectiveness, an area that remains relatively underexplored in private-sector research within the Indonesian context. Practically, the findings provide strategic insights for organizational leaders and managers in designing policies that strengthen employee productivity, reduce operational risk, and enhance accountability through improved internal control mechanisms.